Long‐term outcomes of sensitized lung transplant recipients after peri‐operative desensitization. Issue 10 (15th June 2021) - Aversa, Meghan; Martinu, Tereza; Patriquin, Christopher; Cypel, Marcelo; Barth, David; Ghany, Rasheed; Ma, Jin; Keshavjee, Shaf; Singer, Lianne G.; Tinckam, Kathryn
Abstract : The Toronto Lung Transplant Program has been using a peri‐operative desensitization regimen of plasma exchange, intravenous immune globulin, and antithymocyte globulin in order to accept donor‐specific antibody (DSA)‐positive lung transplants safely since 2008. There are no long‐term data on the impact of this practice on allograft survival or the development of chronic lung allograft dysfunction (CLAD). We extended our prior study to include long‐term follow‐up of 340 patients who received lung transplants between January 1, 2008 and December 31, 2011. We compared allograft survival and CLAD‐free survival among patients in three cohorts: DSA‐positive, panel reactive antibody (PRA)‐positive/DSA‐negative, and unsensitized at the time of transplant. The median follow‐up time in this extension study was 6.7 years. Among DSA‐positive, PRA‐positive/DSA‐negative, and unsensitized patients, the median allograft survival was 8.4, 7.9, and 5.8 years, respectively ( p = .5908), and the median CLAD‐free survival was 6.8, 7.3, and 5.7 years, respectively ( p = .5448). This follow‐up study confirms that long‐term allograft survival and CLAD‐free survival of patients who undergo DSA‐positive lung transplants with the use of our protocol do not differ from other lung transplant recipients. Use of protocols such as ours, therefore, may improve access to transplant for sensitized candidates. Abstract : Six years after the Toronto Lung Transplant Program first reported early outcomes of a peri‐operative desensitization protocol, this follow‐up study confirms comparable long‐term allograft survival and CLAD‐free survival for patients positive compared to negative for donor‐specific antibody.